Valorization of Friedel's salt generated from chloride-containing wastewater treatment through reconstruction into a cobalt-based catalyst for PMS activation - Zhiyu Wei; Zhen Zhou; Xiaohui Ge; Bin Zhou; Enchao Li; Jinyan Qin; Huangwei Deng; Zhenliang Liao (Desalination, 2026)

Comprehensive analysis and therapeutic implications of prognostic value of circadian rhythm genes in hepatocellular carcinoma - Jichun Sun; Jiaxing Hou; Hongbo Xu; Zhiqiang Li; Zhen Deng; Zhi Yang; Wuqing Cao; Junning Hou; Xiaoxin Jin (Journal of Physiology and Biochemistry, 2026)

A Neoproterozoic arc-backarc system in the northern Yangtze Block: Implications for crustal growth and Rodinia reconstructions - Chao Chen; Hao Deng; Jin-Ling Yuan; Timothy Kusky; Qiang Chen; Zhen-Bing She; Ling-Yao Kong; Jiang Zhu; Hong-Mei Li; Jing-Meng Huang; Guo-Hu Wang; Cheng Yang; et al. (Earth-Science Reviews, 2026)

Intensifying aridity shapes network patterns of soil bacterial communities and geographical distribution of sensitive functional groups in grasslands and farmlands on the Loess Plateau - Jia Wang; Xinyi Guo; Yuru Gao; Kang Zhang; Zhen Yang; Xin Zhao; Jushui Hu; Junyao Deng; Jiaqing Liu; Li Li; Peng Shi; Yanbing Lin; et al. (Applied Soil Ecology, 2026)

A pair of newly isolated terpenylated coumarins from Notopterygium incisum roots with anti-inflammatory activity - Li-Lian Zhao; Fei-Yuan Deng; Li Huang; Wei-Jun Dong; Wei-Zhen Dong; Li-Jun Huang; Yun Deng; Da-Le Guo (Phytochemistry Letters, 2026)

Identification, characterization, and projection of meteorological and hydrological compound dry-wet events in Southeast China: A coupled VIC-CMIP6 framework for the Minjiang River Basin - Ze-Jia Li; Zi-Mei Yang; Zhen-Yu Zhang; Ying Chen; Xing-Wei Chen; Lu Gao; Hai-Jun Deng; Mei-Bing Liu (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Decoding the thermocyclic solar-driven fermentation: Multi-omics insights into microbial and metabolic dynamics of traditional Chishui river basin soy sauce - Wei-Qin Deng; Zhen-Ming Lu; Xiong-Bo Li; Zhi-Yi Fan; Ting Li; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Qi-Sheng Zhang; Jin-Song Shi; Gong Chen; Zheng-Hong Xu (Food Chemistry, 2026)

Inverse identification of wind turbine horizontal thrust on steel-concrete hybrid tower using intelligent algorithm - Shou-Zhen Li; Yu-Hang Wang; Jinjin Wang; Ran Deng; Chao Hu; Liming Jiang (Engineering Structures, 2026)

Moisture transport patterns over the Northeastern Tibetan Plateau revealed by tree-ring δ18O records - Kai Wang; Xiaohua Gou; Takeshi Nakatsuka; Yiran Zhang; Jiangzhou Feng; Linlin Gao; Tao Wang; Yang Deng; Zhen Li; Kaixuan Yang; Xuan Li; Chongshan Wang; et al. (Journal of Hydrology, 2026)

Low-frequency deficit irrigation in a semi-arid vineyard of Xinjiang's Manas region: Effects on grape and wine aroma composition across three vintages - Ning Shi; Meng-Bo Tian; Hao-Cheng Lu; Yi-Fan Zhao; Ming-Yu Li; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Zhen-Zhen Zhang; Keji Yu; Yi-Bin Lan; Fei He; et al. (Food Research International, 2026)

Study on oxidative stress and nitric oxide response mechanisms in Gymnodinium sp. under polystyrene microplastic stress - Zhen Ren; Zheng–Xin Hu; Xue Deng; Pei–Feng Li; Chun–Ying Liu; Shan–Shan Duan; Xiang–Feng Kong; Gui–Peng Yang (Journal of Applied Phycology, 2026)

UniPept: A Universal Model for Predicting Peptide Properties Based on Atom-Residue Dual-Scale Integration - Haoshuang Wu; Yu Deng; Zhen Li; Mingming Qi; Yanshi Wei; Linlin Zhuo; Quan Zou; Wenqian Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Trichodermine A, a new polyketide from the endophytic Trichoderma sp. MH550506.1 associated with Gardenia jasminoides - Yan-Li Zhang; Jie-Zhen Shi; Tong-De Zhao; Han-Wei Ruan; Ju-Cheng Zhang; Jin-Hua Yu; Da-Mei Wang; Li-Feng Wang; Liang Deng; Dong Gan; Zhong-Tao Ding (Phytochemistry Letters, 2026)

The impact of low ambient pressure on the cavitation erosion intensity of aluminum alloy materials - Jian-Bo Li; Yong Xia; Wei-Lin Xu; Jun Deng; Jun Chen; Zhen-Yu Du (Ocean Engineering, 2026)

Thermodynamic-kinetic integrated analysis of heat exchanger scaling and control techniques: A case study from a potash processing plant in northwest China - Qian Zheng; Hengtao Deng; Zhen Wang; Huanhuan Song; Ling Xia; Gao Tang; Shaojie Huang; Zhuolin Xie; Yingying He; Hang Li; Nasriddinov Zamoniddin; Hojiev Saidmukbil; et al. (Journal of Cleaner Production, 2026)

Practical applications of graphene-based flexible adhesive respiratory monitoring sensor for daily and clinical monitoring - Deqiang Zhang; Shengtian Mu; Wenhua Wu; Qinqin Xu; Zhen Zheng; Yang Li; Xinkai Deng (Chemical Engineering Journal, 2026)

Sandstone alternation as revealed by spheroidal weathering in the Carboniferous Taiyuan Formation of Shimenzhai Area, Liujiang Basin - Shiqiang Xia; Hongwen Deng; Zhen Liu; Nadeem Ahmad; Taotao Yan; Wei Wu; Quan Li; Guiyu Dong; Haigang Lao; Xiaoying Han; Bin Gao (Applied Geophysics, 2026)

Two newly isolated compounds from Hansenia weberbaueriana and their anti-inflammatory potential - Jie Li; Su Hu; Li Huang; Li-Lian Zhao; Li-Jun Huang; Wei-Jun Dong; Wei-Zhen Dong; Yun Deng; Da-Le Guo (Natural Product Research, 2026)

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

EasyAphid: a comprehensive method for aphid infestation quantification in wheat using EVC-YOLO-Seg model and RGB images - Haotian Deng; Hui Deng; Jiawei Chen; Xin Liu; Zijun Pei; Chenzhao Gao; Qi Sun; Xin Zhang; Shijie Zhai; Xueli Hu; Shuming Fan; Xiao Wang; et al. (Computers and Electronics in Agriculture, 2026)

Numerical Investigation of Natural Gas Pipeline Physical Explosions with a Compressibility-Factor-Based Non-Ideal Initial State Correction - Wenwen Li; Yuguang Cao; Ying Zhen; Qiqi Deng; Hongtu Lu; Zikang Liu (Process Safety and Environmental Protection, 2026)

Pulsed vacuum drying remodels the texture of dried jujube by regulating low-methylesterified pectin and Ca2+-mediated egg-box structures - Xiao-Xiao Niu; Ming-Qiang Xu; Jozef Mravec; Wei-Peng Zhang; Li-Zhen Deng; Guo-gang Chen; Wei-qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

An H3K27la-mediated epigenetic pathway programs myofiber type and meat quality in goats - Zhen Zhang; Xiaohua Zhou; Xinai Huang; Yue Yang; Kaiping Deng; Jun Zhou; Zhipeng Liu; Jingzheng Li; Dongxu Li; M.A. El-Samahy; Guomin Zhang; Yixuan Fan; et al. (Food Chemistry, 2026)

First fossil fruit of Spatholobus (Papilionoideae, Fabaceae) from East Asia - Yi-Shan Zhao; Zhen-Dong Cao; Jing-Nan Huang; Zi-Yi Li; Torsten Wappler; Zhen-Xian Zhang; Shu-mei Xiao; Wei-Yu-Dong Deng; San-Ping Xie (Review of Palaeobotany and Palynology, 2026)

Distribution patterns of potential soil phytopathogenic fungi and their association with plant communities in natural broadleaved forests - Jin Li; Wei Cong; Haimang Yu; Jing Cong; Yuan Yang; Zhen Li; Ye Deng; Kai Feng; Yuguang Zhang (Plant and Soil, 2026)

Efficient paired indirect electrosynthesis of adipic acid from phenol using polyoxometalate electrolytes - Wensi Tang; Zhongling Lang; Ruiqi Yao; Tianyu Qiu; Yonghui Wang; Huaqiao Tan; Wei Liu; Zhen Sun; Zhichao Sun; Yingqi Li; Yangguang Li; Yulin Deng (Science Bulletin, 2026)

Construction of PtRu/Nb2O5 catalysts with high performance and good water- and chlorine-tolerance for the synergistic oxidative removal of multi-component VOCs - Meiyue Li; Qinpei Sun; Yiwen Jia; Jiguang Deng; Zhiquan Hou; Lu Wei; Zhen Wei; Lin Jing; Liangshi Wang; Yuxi Liu; Hongxing Dai (Journal of Environmental Sciences, 2026)

Bidirectional shear-flow preparing lamellar graphene skeletons for tough and conductive nacre-like nanocomposites - Yicong Qin; Gangfeng Cai; Songhan Shi; Haodong Yang; Zihao Deng; Chendong Ge; Peng Li; Chao Gao; Zhen Xu (Chemical Engineering Journal, 2026)

Corrigendum to “Space object classification based on non-conservative force” [Adv. Space Res. 77(6) (2026) 7067–7085] - Zhen Li; Yunlong Deng; Chuang Shi; Qikai Guo; Zhenghang He (Advances in Space Research, 2026)

Genome-Wide Identification, Evolution, and Expression Analysis of the YABBY Gene Family in Cultivated and Wild Soybean - Zhen Liu; Zengzhen Shang; Jiaying Cao; Sainan Zhang; Qian Deng; Haoyang Shi; Yuquan Zhu; Tingke Li; Cheng Guo; Mengting Lei; Man Lv; Tao Wang (Tropical Plant Biology, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Evaluating the role of onboard carbon capture and storage system in remedial unit balancing under the IMO net-zero framework: Insights from GFI and 4E analysis - Yihang Zhou; Shuai Deng; Zhen Tian; Ke Li; Meng Lin; Li Zhao; Chunfeng Li; Xiaohan Zhao; Yijiang Tian; Wenjing Zhang; Min Shi (Journal of Cleaner Production, 2026)

Integrated transcriptomic and metabolomic analyses reveal the antibacterial mechanism of whey fermentation powder against Bacillus cereus L18 and its efficacy in Liangpi preservation - Shijia Fan; Jie Wang; Jieyue Zhou; Zhimin Deng; Pai Peng; Xiaojie Wang; Zequn Zhang; Zhen Li; Biao Suo (Food Research International, 2026)

Mechanistic insights into structural evolution of goji berry (Lycium barbarum L.) during pulsed vacuum drying procedure via moisture migration and cell wall polysaccharide transformations - An-An Zhang; Li-Zhen Deng; Long Xie; Ze-Kang Peng; Ming-Qiang Xu; Wan-Liang Hao; Yu-Hao Jiang; Wen-Bin Ze; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

The intra-annual tree-ring δ18O records from the northeastern Tibetan Plateau can reflect seasonal variations of relative humidity and the intra-annual distribution of precipitation - Kai Wang; Xiaohua Gou; Takeshi Nakatsuka; Yiran Zhang; Tao Wang; Linlin Gao; Yang Deng; Zhen Li; Kaixuan Yang; Xuan Li; Chongshan Wang; Zibo Wang (Agricultural and Forest Meteorology, 2026)

Space object classification based on non-conservative force - Zhen Li; Yunlong Deng; Chuang Shi; Qikai Guo; Zhenghang He (Advances in Space Research, 2026)

Whole-grain black rice diet rewires the single-cell transcriptomic landscape of age-related ovarian decline in mice - Yi-Xuan Tu; Dan-Yang Wang; Jun Ma; Ke-Chun Yu; Sheng-Hui Li; Bo-Han Li; Xin-Yin Deng; Shan Li; Hong-Kai Wang; Tailang Yin; Ling Wang; Zhen-Xia Chen (Science China Life Sciences, 2026)

Discovery and optimization of AAK1 inhibitors based on 1H-indazole scaffold for the potential treatment of SARS-CoV-2 infection - Zi Hui; Haowen Deng; Yueying Xu; Yuan Gao; Chenfeng Zhai; Nian-Dong Mao; Hao Che; Zhen Li; Yuting Zhang; Hang Zhang; Tian Xie; Xiang-Yang Ye (Molecular Diversity, 2026)

Betaine and its key metabolic genes can improve the resistance of Crassostrea hongkongensis to high-salt stress - Zhicai She; Lingxin Kong; Qiong Deng; Tingting Li; Yangyang OuYang; Ziao Chen; Zhen Jia; Hao Qian; Ruiqi Yang; Peng Zhu; Youhou Xu (Aquaculture, 2026)

Sulfite exporter SsTauE enhances bacterial feather degradation by maintaining sulfur homeostasis - Lei Wu; Ming-Shu Zhang; Zhen-Dong Yang; Zhi-Wei Li; Jun-Jin Deng; Xiao-Chun Luo (International Biodeterioration & Biodegradation, 2026)

Genomic, transcriptional and proteomic clarification of fathead minnow and common carp composition in epithelioma papulosum cyprini (EPC) cell line - Bo Li; Jing Hao Yuan; Yu Hang Deng; Shan Nan Chen; Meng Yao Ji; Xu Jia Zhang; Yang Liu; Zhen Gan; Pin Nie; Lan Hao Liu (Fish & Shellfish Immunology, 2026)

Revealing the complex relationship between urbanization and soil erosion by water in China - Wei Li; Keke Li; Jingyu Wang; Wenxing Yang; Zhongci Deng; Yuemin Yang; Cai Li; Zhiyi Li; Zhen Wang (Environmental Impact Assessment Review, 2026)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Catalytic vermiculite membranes tuned by nanoconfined cation and inherent Fe redox relay for millisecond water purification - Lina Zhang; Zhen Qi; Fangzhou Li; Jia Deng; Wulin Yang; Guanghe Li; Fang Zhang (Journal of Hazardous Materials, 2025)

Ionic liquid-amine biphasic solvent characterized by rapid phase separation and low viscosity for efficient CO2 capture - Jinyang Li; Yanxi Deng; Bingling Yuan; Zhengrong Wang; Yongfeng Bai; Zhoulan Huang; Simi Li; Xudong Yang; Guojun Li; Zhen Chen; Junhua Li (Chemical Engineering Journal, 2025)

Butein attenuates cardiac fibrosis by mediating TGF-β1/Smad signaling pathway after myocardial infarction - Mengmeng Deng; Rui Ma; Jinlei Li; Pan Lu; Rong Tan; Zhen Chen; Xin Guo (Journal of Molecular Histology, 2025)

Arsenopyrite reveals the deuteric origin of the Saxi tungsten deposit, SW China - Wanbo Li; Mingguo Deng; Qiang Weng; Wenchang Li; Zhen Jia; Wenbo Song; Zhengrong Li; Jiafei Yang (Acta Geochimica, 2025)

Comprehensive analysis of microbial communities, metabolites, and biogenic amines in bagged fermented chili paste at varying salt levels - Wei-Qin Deng; Zhen-Ming Lu; Ze-Liang Wang; Si-Qiang Jiang; Xiong-Bo Li; Zhi-Yi Fan; Xiao-Juan Zhang; Li-Juan Chai; Qi-Sheng Zhang; Jin-Song Shi; Gong Chen; Zheng-Hong Xu (Food Bioscience, 2025)

From micro-motion to joint monitoring: Fiber-based strain sensors with unmatched sensitivity for flexible wearables - Fan Bu; Ke Liu; Zihui Liang; Jing Li; Jinghan Zeng; Xiaohong Liao; Lang Yang; Yun Deng; Zhen Wang; Yahui Ren; Changhai Yi (Chemical Engineering Journal, 2025)

Phage-host synergy facilitates transformation of dissolved organic matter in simulated composting - Meihua Zhao; Ziwei Deng; Xiaoqin Zhou; Zhen Yu; Li Zhuang (Chemical Engineering Journal, 2025)

Factors of smallholder engagement in forest management: a case in a hilly region in Southwestern China - Wenxing Yang; Cai Li; Zhongci Deng; Wei Zhou; Jingyu Wang; Wei Li; Xiao Zhang; Zhen Wang (Environment, Development and Sustainability, 2025)

Surficial sedimentary properties of Makran accretionary prism and its application to natural gas hydrate distribution - Haifeng Wang; Liang Yi; Fenlian Wang; Yibing Li; Yun Cai; Zhen Zhang; Miao Yu; Xianze Deng; Yong Yang; Huiqiang Yao; Xiguang Deng; Gaowen He (Frontiers in Marine Science, 2025)
The Makran accretionary prism (MAP) resulted from the low-angle, slow-rate subduction of the Arabian Plate beneath the Eurasian Plate. The MAP is an active continental margin, with natural gas hydrate (NGH). In this study, we report an integrated study on surficial sediments, in terms of sediment grain-size, clay minerals and elements. The main results are as follows: (1) the surficial sediments were mainly controlled by hydrodynamic conditions of the Indus River. Along the Indus River channel, it is mainly infilled with silt, while clays are mainly distributed in the accretionary prism. The turbidity records gradually decrease from east to west, along the Indus River channel. (2) Illite and chlorite are the dominate clay minerals, indicating that the surficial sediments were mainly from weathering processes in the Himalaya by the Indus River transport. The very-low contents of kaolinite and smectite indicate the lack of sediments from the Deccan Traps and the in situ hydrothermal materials. (3) Elements analysis indicates that elements Al, Mg, K, Fe, and Ti were terrigeneous, mainly distributed in the northern MAP, while elements Ca and P were from biogenic sources, mainly distributed in the southern part of the study area. In addition, elements U and Mo distribute generally coupled with bottom simulating reflector (BSR), which can be used as proxies of NGH identification. Therefore, we proposed that the covariation between NGH distribution, BSR identification, and trace elements Mo and U holds the potentials in NGH investigation.

Utilizing UAV-based high-throughput phenotyping and machine learning to evaluate drought resistance in wheat germplasm - Xiaojing Zhu; Xin Liu; Qian Wu; Mengshi Liu; Xueli Hu; Hui Deng; Yun Zhang; Yunfeng Qu; Baoqi Wang; Xiaoman Gou; Qiongge Li; Changsheng Han; et al. (Computers and Electronics in Agriculture, 2025)

A pair of lignans isolated from Trachelospermum jasminoides and their anti-inflammatory activity - Chen-Yi Yan; Miao Wang; Yu-Ting Mu; Li-Lian Zhao; Yu-Liang Guo; Wei-Zhen Dong; Yun Deng; Da-Le Guo (Phytochemistry Letters, 2025)

Hydroxy-α-sanshool induces ferroptosis in renal cells via NF-κB/NGAL axis-driven lipid peroxidation - Fajian Ren; Sheng Hu; Xinyi Zhou; Hua Deng; Ziyi Li; Yan Huang; Qiwen Xiang; Tingting Hu; Zhen Tan; Chaolong Rao; Yan Chen (Food Bioscience, 2025)

Highly efficient and sustainable bioconversion of cottonseed meal to high-value products through solid-state fermentation by protease-enhanced Streptomyces sp. SCUT-3 - Zhen-Jie Dai; Ming-Shu Zhang; Zhi-Wei Li; De-Lin Lu; Lei Wu; Can Qin; Hai-Ning Wang; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

RsRCO and RsLMI1 co-regulate the formation of lobed leaf in radish (Raphanus sativus L.) - Qian Yang; Lei Cui; Xiaoyao Li; Zhaoxin Peng; Haoyan Sun; Caixia Gan; Zhen Hu; Zhixiong Liu; Zhenbiao Jiao; Zhengming Qiu; Chenghuan Yan; Xiaohui Deng (Theoretical and Applied Genetics, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Three new aliphatic compounds from the roots of Saposhnikovia divaricata and their antiproliferative activity on HepG2 cells - Yan Liu; Jin-Hong Xue; Yan Sun; Fan-Ying Deng; Si-Yi Wang; Juan Pan; Zhi-Chao Hao; Ke-Zhen Chen; Anam Naseem; Qing-Shan Chen; Li-Li Zhang; Hai-Xue Kuang; et al. (Natural Product Research, 2025)

Integrating morphology, ecology, and genomics: Unraveling the population genetic and evolution within the Rosa graciliflora complex - Jia Miao; Liang-Ying Li; Zhen-Long Liang; Yu Feng; Cheng Zhang; Shi-Qi Li; Heng-Ning Deng; Jian Ru; Zhong-Yu Tang; Xin-Fen Gao (Molecular Phylogenetics and Evolution, 2025)

An approach and mechanistic insights of coating-type binders for 4.6 V-LiCoO2 cathode of lithium-ion battery - Li Deng; Yu-Xi Luo; Zhen Wang; Jin-Xia Lin; Jun-Ke Liu; Kun-Gui Zheng; Gao-Yang Bai; Zu-Wei Yin; Yao Zhou; Jun-Tao Li (Chemical Engineering Journal, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Probiotics: A New Approach for the Prevention and Treatment of Cervical Cancer - Hui Li; Zhen Xu; Chaoqi Liu; Jinfang Deng; Ziqin Li; Yongqin Zhou; Zhiying Li (Probiotics and Antimicrobial Proteins, 2025)

Flavobacterium aestuarii sp. nov., a novel species isolated from the Pearl River Estuary - Qi Li; Zi-Qi Peng; Hong-Chuan Wang; Lei Dong; Dan-Yuan Guo; Pan-Deng Wang; Xiao-Qing Luo; Zhen-Hao Luo; Zi-Wen Yang; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

An oral recombinant human type 5 adenovirus vector vaccine encoding the S protein of Type I feline coronavirus effectively protection against FCoV challenge in cats - Gu-nan Deng; Chang-zhan Xie; Ke-lei Zhou; Chun-sai He; Yuan-Zhen Ma; A.-jia Ake; Rui Guo; Kai Li; Chen Peng; Bin Zhang (Veterinary Microbiology, 2025)

Variations in 3-chloropropanol esters, glycidyl esters, and lipid accompaniments during the simulated moderate decolorization process of maize germ oil - Yu Jie Wang; Li Li Xu; Ai Zhen Zong; Fang Ling Du; Deng Yu Xie; Yun Qi Wen; Tong Cheng Xu (Food Chemistry, 2025)

Carbon dioxide reduction through mineral carbonation by steel slag - Yongpeng Zhang; Yimei Ying; Lei Xing; Guoxiong Zhan; Yanli Deng; Zhen Chen; Junhua Li (Journal of Environmental Sciences, 2025)

Slope unit-based comprehensive geohazard susceptibility assessment: SHAP interpretability and local InSAR deformation analysis - Peng Wang; Hongwei Deng; Jielin Li; Zhen Jiang; Guanglin Tian; Yao Liu (Advances in Space Research, 2025)

Seismic Prediction of Shallow Unconsolidated Sand in Deepwater Areas - Jiale Chen; Yingfeng Xie; Tong Wang; Haoyi Zhou; Zhen Zhang; Yonghang Li; Shi Zhang; Wei Deng (Journal of Marine Science and Engineering, 2025)
Recently, shallow gas fields and hydrate-bearing sand in the deepwater area of the northern South China Sea have been successively discovered, and the accurate prediction of shallow sands is an important foundation. However, most of the current prediction methods are mainly for deep oil and gas reservoirs. Compared with those reservoirs with high degree of consolidation, shallow sandy reservoirs are loose and unconsolidated, whose geophysical characteristics are not well understood. This paper analyzes the logging data of shallow sandy reservoirs recovered in the South China Sea recently, which show that the sand content has a significant influence on Young’s modulus and Poisson’s ratio of the sediments. Therefore, this paper firstly constructs a new petrophysical model of unconsolidated strata targeting sandy content and qualitatively links the mineral composition and the elastic parameters of the shallow marine sediments and defines a new indicator for sandy content: the modified brittleness index (MBI). The effectiveness of MBI in predicting sandy content is then verified by measured well data. Based on pre-stack seismic inversion, the MBI is then inverted, which will identify the sandy deposits. The method proposed provides technical support for the subsequent shallow gas and hydrate exploration in the South China Sea.

Metabolomics and sensory evaluation reveal the influence of four albino tea cultivars on the quality of processed green tea - Yifan Li; Zhen Han; Miao Wang; Yaxing Yan; Ruihong Ma; Hongping Wang; Wei-Wei Deng (Food Research International, 2025)

Investigation on fluorescence enhancement of DNA tetrahedral structures modified DNA-silver nanoclusters for biosensing - Boyuan Jia; Xuesong Li; Xinyu Wang; Yanyan Lu; Hui Meng; Xinshuo Zhang; Xiangyang Wu; Zhen Zhang; Yibin Deng (Chemical Engineering Journal, 2025)

Genesis of the Yunlong Sn deposit in the Chongshan Shear Zone, Western Yunnan, SW China - Zhen Jia; Wenchang Li; Jianze Sha; Shiping Li; Fuchuan Chen; Mingguo Deng (Journal of Geochemical Exploration, 2025)

Petrogenesis of Ke’eryin granitic pegmatites and associated Li mineralization in the Songpan–Ganze orogenic belt, China: evidence from apatite and bulk-rock chemistry - Qing-Gao Yan; Jian-Kang Li; Deng-Hong Wang; Ze-Ying Zhu; Chao Li; Zhen-Yu Chen (Mineralium Deposita, 2025)

Nitrogenous chemical constituents and their antitumor activities evaluation in vitro from the aerial parts of Corydalis impatiens (pall.) Fisch - Ze-dong Nan; Yi-dong Zhu; Chao-fan Deng; Guo-dong Jiang; Zhen-zhen Wang; Chong-long Li; Xiao-li Ma; Zhi-Bo Jiang (Natural Product Research, 2025)

Robust mussel-inspired LBL carbon nanotube-based superhydrophobic polyurethane sponge for efficient oil–water separation utilizing photothermal effect - Guoyan Yang; Yuxin Zhang; Zuozhu Yin; Yuanting Deng; Zihao Li; Yu Xie; Yuhua Chen; Chenggang Yang; Haitao Yang; Yidan Luo; Zhen Hong; Mingshan Xue (Fuel, 2025)

Machine learning-based strength prediction for circular concrete-filled double-skin steel tubular columns under axial compression - Shou-Zhen Li; Jin-Jin Wang; Liming Jiang; Ran Deng; Yu-Hang Wang (Engineering Structures, 2025)

Enzyme memory-driven Ce-enhanced carbon dots from vegetable moss enable rapid treatment of traumatic spinal cord injury - Baofeng Zhao; Fan Wang; Huicong Feng; Jiacheng Sun; Dake Wang; Pengfei Zhuang; Zhanpeng Guo; Yu Deng; Zhen Dai; Yuan Wang; Dan Li; Xifan Mei (Chemical Engineering Journal, 2025)

Thermophilic bacteria contributing to humus accumulation in hyperthermophilic aerobic fermentation of mushroom residue - Xiaoqin Zhou; Zhen Yu; Kaipeng Zhai; Wenkang Deng; Li Zhuang; Yueqiang Wang; Qiang Zhang; Shungui Zhou (Bioresource Technology, 2025)

Sensing array based on imidazole-regulated Cu@MOFs nanozymes with enhanced laccase-like activity for the discrimination of phenolic pollutants - Fang Zhu; Mengfan Li; Yudi Yang; Fengxiang Ai; Yunxiang Fan; Chunmeng Deng; Kun Zeng; Dali Wei; Yibin Deng; Zhen Zhang (Analytica Chimica Acta, 2025)

Foliar uptake, translocation and its contribution to Cadmium accumulation in rice - Zhen Zhu; Jianwei Peng; Pengyue Yu; Jiangchi Fei; Zhi Huang; Yaocheng Deng; Xiaoe Yang; Jipeng Luo; Tingqiang Li; Ying Huang (Science of The Total Environment, 2025)

Corrigendum to “Transformation of cell wall pectin profile during postharvest ripening process alters drying behavior and regulates the sugar content of dried plums” [Food Chem. 458 (2024) 140093] - Xiao-Xiao Niu; Li-Zhen Deng; Haiou Wang; Qing-Hui Wang; Ming-Qiang Xu; Suo-Bin Li; Samuel Ariyo Okaiyeto; Hong-Wei Xiao (Food Chemistry, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Oxygen vacancy-modified fast charge transport channels at the interface of bismuth S-scheme heterojunctions promoting photocatalytic performance - Jiawei Liu; Zhilin Zhang; Junhao Lin; Li Zhen; Qingyang Jiang; Jun Shi; Huiping Deng (Chemical Engineering Journal, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

Hyperthermophilic composting coupled with vermicomposting stimulates transformation of organic matter by altering bacterial community - Xiaoqin Zhou; Zhen Yu; Wenkang Deng; Ziwei Deng; Yueqiang Wang; Li Zhuang; Shungui Zhou (Science of The Total Environment, 2024)

A novel 0D/2D Z-scheme heterojunction Bi2Sn2O7/Bi4O7 for boosting tetracycline photodegradation: Insight from performance to mechanism - Li Zhen; Yongsui Xu; Jiawei Liu; Zizhen Wu; Jun Shi; Huiping Deng (Journal of Water Process Engineering, 2024)

Multi-plateau water adsorption of pyrene-based covalent organic frameworks for potential humidity control - Tianyi Liu; Pengfei Cheng; Jiaojiao Liu; Li Yang; Zhen Li; Yimeng Li; Weiqiao Deng (Chemical Engineering Journal, 2024)

Promotion of aromatic amino acids of extracellular polymeric substance targeted transformation via sulfite mediated iron redox cycling in sludge solid-liquid separation - Jiahao Lai; Huan Liu; Zhen Yang; Rong Deng; Yun Xiong; Yafei Li; Min Song (Water Research, 2024)

Intercomparison of measured and modelled photochemical ozone production rates: Suggestion of chemistry hypothesis regarding unmeasured VOCs - Jun Zhou; Wenjie Wang; Yan Wang; Zhen Zhou; Xiongzhou Lv; Meijin Zhong; Bowen Zhong; Minhui Deng; Bin Jiang; Junqing Luo; Jiahua Cai; Xiao-Bing Li; et al. (Science of The Total Environment, 2024)

Transformation of cell wall pectin profile during postharvest ripening process alters drying behavior and regulates the sugar content of dried plums - Xiao-Xiao Niu; Li-Zhen Deng; Haiou Wang; Qing-Hui Wang; Ming-Qiang Xu; Suo-Bin Li; Samuel Ariyo Okaiyeto; Hong-Wei Xiao (Food Chemistry, 2024)

Smartphone assisted paper strip-based colorimetric sensing of phosphate and copper ions utilizing bi-ligand intercalated cobalt-MOF as a dual functional nanozyme - Arunjegan Amalraj; Ravikumar Ayyanu; Rajaji Pavadai; Tamil Selvan Govindaraj; Emmanuel Chigozie Aham; Xuesong Li; Yibin Deng; Zhen Zhang (Journal of Environmental Chemical Engineering, 2024)

Transformation of dissolved nitrogen under UV/H2O2: A review on composition, behavior and potential risk - Yongsui Xu; Ning Yang; Sicheng Gong; Haoyu Guo; Jiawei Liu; Li Zhen; Zizhen Wu; Zhilin Zhang; Jia Liu; Jun Shi; Huiping Deng (Journal of Environmental Chemical Engineering, 2024)

Surface to bulk design empowering Ni-rich layered oxide cathode in sulfide-based All-Solid-State batteries - Yuanyuan Li; Jianwei Li; Zhen Zeng; Xiao Xu; Jun Cheng; Hongqiang Zhang; Jing Li; Yiwei Rao; Ying Deng; Lijie Ci; Deping Li (Chemical Engineering Journal, 2024)

Insight into photocatalytic chlortetracycline degradation by WO3/AgI S-scheme heterojunction: DFT calculation, degradation pathway and electron transfer mechanism - Chuantao Wang; Xiang Li; Xueting Lv; Xin Huang; Yueyue Zhao; Tiantian Deng; Jiale Zhang; Jun Wan; Yanzhong Zhen; Tuo Wang (Journal of Cleaner Production, 2024)

Hierarchical supramolecules composed of starch-based nanocluster aggregates with light-responsive mechanical strain for remotely rapid and precise actuation - Fu-Xiang Wei; Xu Yuan; Feng-Qiong Jiang; Zhen Wang; Yong-Fu Deng; Chuan-Hui Xu; Li-Hua Fu; Bao-Feng Lin (Carbohydrate Polymers, 2024)

Stability of tryptophan-containing LOs in flaxseed oil and their response towards γ-tocopherol - Wan-zhen Li; Zi-liang Song; Jun-le Li; Jia-hui Yu; Du-jian Deng; Xiao-qing Cai; Martin J.T. Reaney; Zi-zhe Cai; Yong Wang (Food Chemistry, 2024)

Identifying the Interaction Between Tuberculosis and SARS-CoV-2 Infections via Bioinformatics Analysis and Machine Learning - Ze-Min Huang; Jia-Qi Kang; Pei-Zhen Chen; Lin-Fen Deng; Jia-Xin Li; Ying-Xin He; Jie Liang; Nan Huang; Tian-Ye Luo; Qi-Wen Lan; Hao-Kai Chen; Xu-Guang Guo (Biochemical Genetics, 2024)

The complete degradation of 1,2-dichloroethane in Escherichia coli by metabolic engineering - Yong-Dong Deng; Wen-Hui Zhang; Zhi-Hao Zuo; Hao Zhang; Jing Xu; Jian-Jie Gao; Bo Wang; Zhen-Jun Li; Xiao-Yan Fu; Li-Juan Wang; Yu Wang; Yong-Sheng Tian; et al. (Journal of Hazardous Materials, 2024)

Two new cytotoxic diterpenoid alkaloids from Delphinium grandiflorum - Ze-dong Nan; Ying Shang; Chao-fan Deng; Yi-dong Zhu; Guo-dong Jiang; Zhen-zhen Wang; Chong-long Li; Xiao-li Ma; Zhi-Bo Jiang (Phytochemistry Letters, 2024)

Behavioral responses of Nesidiocoris tenuis (Reuter) to different monochromatic lights and light intensities - Zhen Chen; Wen Fu; Chun-Fu Zhang; Hong-Mei Li; Jun-Jun Zhang; Deng-Ji Lou; Kai-Fei Guo (Journal of Plant Diseases and Protection, 2024)

Live chicken body fat measurement technology based on bio-electrical impedance - Jiaming Zuo; Jinping Liang; Shangshang Cheng; Yuelin Deng; Zhenhui Li; Qinghua Nie; Dexiang Zhang; Xiquan Zhang; Zhen Li; Hongmei Li (Computers and Electronics in Agriculture, 2024)

Emergence of blaNDM-5–bearing IncHI2/ST2 and p0111 multidrug-resistance plasmids and widespread distribution of IncHI2/ST3–blaNDM-5 plasmids across foods, animals, and humans - Lu-Chao Lv; Cheng-Zhen Wang; Jing-Jing Yu; Yan-Xiang Jiao; Li-Min Deng; Wan-Yun He; Guo-Long Gao; Xiao-Yu Zhang; Li-Tao Lu; Xun Gao; Yi-Yun Liu; Jian-Hua Liu (Food Control, 2024)

Ultrahigh energy storage performance in AN-based superparaelectric ceramics - Qibin Liao; Tao Deng; Teng Lu; Zhen Liu; Narendirakumar Narayanan; Song Li; Shiguang Yan; Yizheng Bao; Yun Liu; Genshui Wang (Chemical Engineering Journal, 2024)

Double-Network structure chemically programmed DNA Cryogel: Enzyme immobilization platform with enhanced catalytic activity for portable biosensing - Jiaxuan Xiao; Hui Meng; Yumo Li; Yuhan Wang; Xiaofeng Yang; Xuesong Li; Nuanfei Zhu; Yibin Deng; Yanshen Li; Zhen Zhang (Chemical Engineering Journal, 2024)

Diffusion characteristics of coal dust associated with different ventilation methods in underground excavation tunnel - Yang Xiao; Xue-Er Yang; Zhen-Ping Wang; Qing-Wei Li; Jun Deng (Process Safety and Environmental Protection, 2024)

Secreted salt and hydrodynamic factors combine to affect dynamic fluctuations of microplastics on mangrove leaves - Yihua Wei; Meng Jiao; Zhen Zhao; Liangdong Tang; Yijin Wang; Jun Deng; Gen Peng; Ruilong Li; Yinghui Wang (Journal of Hazardous Materials, 2024)

Enhancement of adsorption performance for I2 and Cr(VI) by the metal-organic framework UiO-66-NH2 via post-synthetic modification - Ya-Yu Zhao; Zhen Xu; Xin Chen; Meng-Qiang Deng; Peng Li; Wei Gao; Ji-Yang Li; Xiu-Mei Zhang (Journal of Environmental Chemical Engineering, 2024)

Spatial and widely targeted metabolomics and anatomical analysis reveal the mechanisms associated with petal bicolor patterning of two Dendrobium species - Mei-Jing Ou; Hong-Yan Li; Han Liang; Zhen-Hai Deng; Zi-Bin Zhang; Jia-Wei Li (Brazilian Journal of Botany, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Perturbation of lipid metabolism in 3T3-L1 at different stages of preadipocyte differentiation and new insights into the association between changed metabolites and adipogenesis promoted by TBBPA or TBBPS - Yun-Jiang Yu; Jing-Lin Tian; Tong Zheng; Hong-Xuan Kuang; Zong-Rui Li; Chao-Jie Hao; Ming-Deng Xiang; Zhen-Chi Li (Journal of Hazardous Materials, 2024)

Sustainable valorizing high-protein feather waste utilization through solid-state fermentation by keratinase-enhanced Streptomyces sp. SCUT-3 using a novel promoter - Wen-Jun Lu; Ming-Shu Zhang; De-Lin Lu; Zhi-Wei Li; Zhen-Dong Yang; Lei Wu; Jing-Tao Ni; Wei-Dong Chen; Jun-Jin Deng; Xiao-Chun Luo (Waste Management, 2024)

Long-term exposure to the mixture of phthalates induced male reproductive toxicity in rats and the alleviative effects of quercetin - Li-Lan Liu; Jun-Zhe Yue; Zhen-Yu Lu; Ru-Ya Deng; Can-Can Li; Ye-Na Yu; Wen-Jin Zhou; Min Lin; Hai-Tao Gao; Jiaming Liu; Ling-Zi Xia (Toxicology and Applied Pharmacology, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Self-dispersed Fe single-atom anchored biochar derived from hyperaccumulator residues with intrinsic Zn and Fe for selective peroxymonosulfate activation via electron transfer process - Fangzhou Li; Ziren Wan; Di Zheng; Lina Zhang; Wan Huang; Fei Chen; Jia Deng; Zhen Qi; Guanghe Li; Fang Zhang (Chemical Engineering Journal, 2024)

Assessing biogeochemical controls on porewater dissolved inorganic carbon cycling in the gas hydrate-bearing sediments of the Makran accretionary wedge, Northeastern Arabian Sea off Pakistan - Yuanqing Chen; Sinan Xu; Weining Liu; Zhen Zhang; Tianbang Yang; Xiao Xiao; Xiguang Deng; Jiangtao Li; Huiqiang Yao; Zijun Wu (Frontiers in Marine Science, 2024)
Quantitatively assessing the porewater dissolved inorganic carbon (DIC) cycling in methane-enriched marine sediments is crucial to understanding the contributions of different carbon sources to the global marine carbon pool. In this study, Makran accretionary wedge was divided into Zone 1 (high methane flux area) and Zone 2 (background area). Porewater geochemical compositions (Cl – , SO 4 2– , NH 4 + , Mg 2+ , Ca 2+ , Ba 2+ , DIC and δ 13 C-DIC) and a reaction-transport model were used to determine the DIC source and calculate the DIC flux through carbonate precipitation and releasing into overlying seawater in sediments. Zone 1 is characterized by the shallower depth of sulfate-methane transition (SMT), where most of porewater sulfate was consumed by anaerobic oxidation of methane (AOM). In contrast, a relatively low flux of methane diffusion in Zone 2 results in a deeper SMT depth and shallow sulfate is predominantly consumed by organoclastic sulfate reduction (OSR). Based on the porewater geochemical profiles and δ 13 C mass balance, the proportions of porewater DIC originating from methane were calculated as 51% in Zone 1 and nearly 0% in Zone 2. An increase of porewater DIC concentration leads to authigenic carbonate precipitation. Solid total inorganic carbon (TIC), X-ray diffractometry (XRD) and scanning electron microscopy (SEM) analysis display that carbonate content increases with depth and aragonite appears at or below the depths of SMT. Meanwhile, the flux of DIC released from sediments calculated by the reaction-transport model is 51.3 ~ 90.4 mmol/m 2 ·yr in Zone 1, which is significantly higher than that in Zone 2 (22.4 mmol/m 2 ·yr). This study demonstrates that AOM serves as the dominant biogeochemical process regulating the porewater DIC cycle, which has an important impact on the authigenic carbonate burial and the seawater carbonate chemistry.

Land-based transportation influences carbon emission in urbanized China: A regional spatial spillover perspective - Chen Zeng; Bingqian Chai; Lindsay C. Stringer; Yangbiao Li; Zhen Wang; Xiangzheng Deng; Binbin Ma; Jinming Ren (Sustainable Cities and Society, 2024)

Sublethal and transgenerational effects of lufenuron on the biological traits of Panonychus citri (McGregor) (Acari: Tetranychidae) - Meng-Hao Xia; Deng Pan; Chuan-Zhen Li; Yu-Chuang Li; Wei Dou; Jin-Jun Wang (Pesticide Biochemistry and Physiology, 2024)

On-demand detachable adhesive hydrogel based on dual dynamic covalent cross-linked with NIR/pH dual-responsive properties for diabetic wound healing - Kaize Su; Duanyu Deng; Xiaoxian Wu; Yumu Song; Ying Sun; Xu Wang; Zhen Zhang; Jinxuan Li; Zhenping Yan; Xiangcun Shang; Chen Li; Kun Zhang; et al. (Chemical Engineering Journal, 2024)

Reducing the risk of missing soil contamination by integrating multi-investigated methods in a retired chrome salt factory - Yun Chen; Dengdeng Jiang; Zhen Song; Jing Wei; Shaohua Cao; Xuwei Li; Yunjin Wu; Shaopo Deng (Journal of Environmental Chemical Engineering, 2023)

High-level production of cordycepin by the xylose-utilising Cordyceps militaris strain 147 in an optimised medium - Liangkun Long; Zhen Liu; Yizhou Wang; Qunying Lin; Shaojun Ding; Chuanhua Li; Chunying Deng (Bioresource Technology, 2023)

Targeting transportation of curcumin by soybean lipophilic protein nano emulsion: Improving its bioaccessibility and regulating intestinal microorganisms in mice - Zhen Zeng; Siqi Deng; Yang Liu; Cheng Li; Zhengfeng Fang; Bin Hu; Hong Chen; Caixia Wang; Saiyan Chen; Wenjuan Wu; Yuntao Liu (Food Hydrocolloids, 2023)

A self-supply crRNA-mediated CRISPR/Cas12a-driven controlled-release homogeneous biosensor for ultrasensitive detection of microRNA - Jiangbo Dong; Shiying Zhou; Yin Liu; Liyuan Deng; Zhen Huang; Jian Chen; Jiawei Li; Changjun Hou; Danqun Huo (Chemical Engineering Journal, 2023)

Bacterial mineralization of chromium-copper spinel with highly performance in electroplating effluent - Zhongxuan Xu; Yuxi Chen; Zhen Wu; Diandi Li; Xiaoqin Li; Xuezhen Feng; Hong Deng; Hong Chen; Bintian Zhang; Zhang Lin (Water Research, 2023)

Volatile organic compounds and metals/metalloids exposure in children after e-waste control: Implications for priority control pollutants and exposure mitigation measures - Hong-Xuan Kuang; Meng-Yang Li; Yang Zhou; Zhen-Chi Li; Ming-Deng Xiang; Yun-Jiang Yu (Journal of Hazardous Materials, 2023)

Wnt/β-Catenin Promotes the Osteoblastic Potential of BMP9 Through Down-Regulating Cyp26b1 in Mesenchymal Stem Cells - Xin-Tong Yao; Pei-pei Li; Jiang Liu; Yuan-Yuan Yang; Zhen-Ling Luo; Hai-Tao Jiang; Wen-Ge He; Hong-Hong Luo; Yi-Xuan Deng; Bai-Cheng He (Tissue Engineering and Regenerative Medicine, 2023)

Rockfall feature investigation and kinematic simulation based on nap-of-the-object photogrammetry and GIS spatial modeling - Xude Li; Fu-zhen Liu; Li Zhao; Na Deng; Long Chen; Jing-shen Pan; Guo-qiang Tang (Natural Hazards, 2023)

An improved vacuum-steam pulsed blanching machine design and garlic scape blanching verified experiment - Jing-Shou Zhang; Xian-Jun Chen; Sara Zielinska; Parag Prakash Sutar; Suo-Bin Li; Li-Zhen Deng; Hui Wang; Yu-Hang Chen; Hong-Wei Xiao (Innovative Food Science & Emerging Technologies, 2023)

Full-temperature all-solid-state dendrite-free Zn-ion electrochromic energy storage devices for intelligent applications - Lei Liu; Mingshuo Zhen; Liyong Wang; Bin Li; Chengfu Deng; Zhixing Zhang; Xiangqian Fan; Ning Li; Huiqi Wang; Chen Li; Shengliang Hu (Chemical Engineering Journal, 2023)

Corrigendum to “Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China” [Sci. Total Environ. 857 (2023) 159337] - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Complete biodegradation of the oldest organic herbicide 2,4-Dichlorophenoxyacetic acid by engineering Escherichia coli - Yu Wang; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Hong-Juan Han; Li-Juan Wang; Wen-Hui Zhang; Yong-Dong Deng; Cen Qian; Zhi-Hao Zuo; et al. (Journal of Hazardous Materials, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Relative influence on cell behaviors of osteoblasts seeded onto demineralized bone matrix with diverse particle size - Li Yang; Hao Zhang; Jie Liu; Jingyu Zhang; Dong Zhen; Biyong Deng; Yongcheng Hu (Cell and Tissue Banking, 2023)

Damage characteristics and dynamic response of steel–concrete-steel composite targets penetrated by a rigid projectile - Chenkang Liu; Hongxiao Wu; Fei Gao; Zhen Wang; Shuxin Deng; Guokai Zhang; Siyuan Yu; Jie Li; Mingyang Wang (Engineering Structures, 2023)

Maternal environmental, occupational, and urinary metabolite levels of benzene compounds and their association with congenital heart diseases in offspring: a case‒control study in China - Meixian Wang; Lu Li; Hong Kang; Hongmei Xu; Qian Huang; Nana Li; Ying Deng; Ping Yu; Zhen Liu (Environmental Science and Pollution Research, 2023)
The conclusions about the association of maternal pregnancy environment, occupation, and benzene compounds with fetal CHD are not entirely consistent. Eight hundred seven CHD cases and 1008 controls were included in this study. All occupations were classified and coded against the Occupational Classification Dictionary of the People’s Republic of China (2015 version). Logistic regressions were used to explore the correlation among environmental factors, occupation types, and CHDs in offspring. We found that living near public facilities and having exposure to chemical reagents and hazardous substances were significant risk factors for CHDs in offspring. We found that offspring of mothers who worked in agriculture and similar work during pregnancy suffered from CHD. The risk of all CHDs in the offspring of pregnant women working in production manufacturing and related work was significantly higher than that in unemployed pregnant women, the risk was also observed in 4 subtypes of CHDs. We compared the concentrations of the five metabolite (MA, mHA, HA, PGA, and SPMA) levels of benzene compounds in the urine of mothers in case and control groups and found no significant differences. Our study suggests that maternal exposure during pregnancy and certain environmental and occupational conditions are risk factors for CHD in offspring, but did not support an association between concentrations of metabolites of benzene compounds in the urine of pregnant women and CHDs in their offspring.

Responses of microbial community to geochemical parameters on vertical depth in bioheap system of low-grade copper sulfide - Xiu-Tong Li; Zhong-Sheng Huang; Ye Huang; Zhen Jiang; Zong-Lin Liang; Hua-Qun Yin; Guang-Ji Zhang; Yan Jia; Ye Deng; Shuang-Jiang Liu; Cheng-Ying Jiang (Science of The Total Environment, 2023)

Co-exposure levels of volatile organic compounds and metals/metalloids in children: Implications for E-waste recycling activity prediction - Hong-Xuan Kuang; Meng-Yang Li; Lei-Zi Li; Zhen-Chi Li; Chuan-Hua Wang; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2023)

Associations between trace level thallium and multiple health effects in rural areas: Chinese Exposure and Response Mapping Program (CERMP) - Yun-Jiang Yu; Zhen-Chi Li; Yang Zhou; Chen-Yin Dong; Hong-Xuan Kuang; Tong Zheng; Ming-Deng Xiang; Xi-Chao Chen; Hong-Yan Li; Xiao-Wen Zeng; Shu-Li Xu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Flexible nitrogen-doped carbon nanofiber-reinforced hierarchical hollow iron oxide nanorods as a binder-free electrode for efficient capacitive deionization - Ming Gao; Jiaxin Li; Yuan Wang; Wencui Liang; Zhiqian Yang; Yi Chen; Wenyang Deng; Zhen Wang; Tianqi Ao; Wenqing Chen (Desalination, 2023)

Aerobic glycolysis in colon cancer is repressed by naringin via the HIF1A pathway - Guangtao Pan; Ping Zhang; Aiying Chen; Yu Deng; Zhen Zhang; Han Lu; Aoxun Zhu; Cong Zhou; Yanran Wu; Sen Li (Journal of Zhejiang University-SCIENCE B, 2023)

Low-noise, low-power-consumption seafloor vector magnetometer - Xiaochen Li; Xianhu Luo; Ming Deng; Ning Qiu; Zhen Sun; Kai Chen (Journal of Oceanology and Limnology, 2023)

Effect of grazing exclusion on emission of greenhouse gases and soil organic carbon turnover in alpine shrub meadow - Zhiqiang Dang; Na Guo; Shanshan Li; A. Allan Degen; Jingjuan Cao; Bin Deng; Aidong Wang; Zhen Peng; Luming Ding; Ruijun Long; Zhanhuan Shang (Science of The Total Environment, 2023)

Highly efficient shrimp shell recovery by solid-state fermentation with Streptomyces sp. SCUT-3 - De-Lin Lu; Ming-Shu Zhang; Jun-Jin Deng; Wen-Jun Lu; Zhen-Dong Yang; Zhi-Wei Li; Yu-Chen Chen; Xiao-Chun Luo (Chemical Engineering Journal, 2023)

Low-tortuosity carbon electrode derived from Wood@ZIF-67 for supercapacitor applications - Zhen Zhang; Songlin Deng; Delong Wang; Yan Qing; Ge Yan; Lei Li; Yiqiang Wu (Chemical Engineering Journal, 2023)

Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Spatiotemporal pattern of the dynamics in area, production, and yield of Aus rice in Bangladesh and its response to droughts from 1980 to 2018 - Arifuzzaman Khondakar; Jinwei Dong; Zhichao Li; Xiangzheng Deng; Mrinal Singha; Md. Mizanur Rahman; Zhenong Jin; Shaoqiang Wang; Lin Zhen; Xiangming Xiao (Journal of Geographical Sciences, 2022)

Long-term changes in zooplankton in the Changjiang estuary from the 1960s to 2020 - Ping Du; Wen-Jian Ye; Bang-Ping Deng; Ming Mao; Yuan-Li Zhu; Fang-Ping Cheng; Zhi-Bing Jiang; Lu Shou; Quan-Zhen Chen (Frontiers in Marine Science, 2022)
The Changjiang estuary (CJE) is a large estuary that is affected by multiple anthropogenic stressors and climate change. The long-term trend of zooplankton in the CJE is an important indicator of the ecological response to stressors. We applied the Mann–Kendall trend analysis and Pettitt test to detect the trend and breakpoints of the biomass of the large mesozooplankton (LMZ; 505–20 000 μm) in four seasons, abundance of main LMZ taxa in summer from the 1960s to 2020, and abundance of dominant species in summer from 2000 to 2020 in the CJE. Results showed that LMZ biomass increased significantly during spring and summer, and the breakpoints both occurred in the 1980s. After the breakpoint, the mean biomass increased from 142.88 to 429.42 mg/m 3 in spring and from 296.28 to 723.92 mg/m 3 in summer. After 2000, the abundance of Copepoda in summer increased by more than 10 times compared to the 1960s. Under the conditions of warming and increased dinoflagellate abundance in the CJE, the abundance of the warm-water and omnivorous small calanoid copepod Paracalanus aculeatus increased significantly. Meanwhile, the significant decrease in the abundance of the temperate brackish species Labidocera euchaeta was probably mainly related to warming. The rapid changes in LMZ biomass during the late 1980s and mid-1990s is probably the result of a combination of enhanced bottom–up support, reduced top–down pressure, and promotion of temperature. This study provides scientific evidence and insights into the adaptive management of the Changjiang Basin.

Sphingopyxis yananensis sp. nov., a novel 2-nitropropane degrading bacterium isolated from a microbial fermentation bed substrate - Chao-chao Zheng; Ying-ying Jiang; Tian-fei Yu; Jing Li; Jia-min Ai; Mai-ping Li; Xiao-dong Liu; Zhen-shan Deng (Archives of Microbiology, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Distinct co-occurrence patterns and driving forces of abundant and rare bacterial communities in the multispecies solid-state fermentation process of cereal vinegar - Ming-Ye Peng; Zhen-Ming Lu; Xiao-Juan Zhang; Ting Huang; Yong-Jian Deng; Li-Juan Chai; Jin-Song Shi; Zheng-Hong Xu (Systems Microbiology and Biomanufacturing, 2022)

Association between congenital heart defects and maternal manganese and iron concentrations: a case–control study in China - Meixian Wang; Yan Tian; Ping Yu; Nana Li; Ying Deng; Lu Li; Hong Kang; Dapeng Chen; Hui Wang; Zhen Liu; Juan Liang (Environmental Science and Pollution Research, 2022)
To investigate the correlation between maternal manganese and iron concentrations and the risk of CHD among their infant. A multi-center hospital-based case control study was conducted in China. There were 322 cases and 333 controls have been selected from pregnant women who received prenatal examinations. Correlations between CHDs and maternal manganese and iron concentrations were estimated by conditional logistic regression. Moreover, the interaction between manganese and iron on CHDs was analyzed. Compared with the controls, mothers whose hair manganese concentration was 3.01 μg/g or more were more likely to have a child with CHD than those with a lower concentration. The adjusted OR was 2.68 (95%CI = 1.44–4.99). The results suggested that mothers whose iron content was 52.95 μg/g or more had a significantly higher risk of having a child with CHD ( aOR = 2.87, 95%CI = 1.54–5.37). No interaction between maternal manganese and iron concentrations was observed in the multiplicative or additive model. The concurrently existing high concentration of manganese and iron may bring higher risk of CHD ( OR = 7.02). Women with excessive manganese concentrations have a significantly increased risk of having offspring with CHDs. The high maternal iron status also correlates with CHDs. The concurrently existing high concentration of manganese and iron may bring higher risk of CHD.

Identification and analysis of oil candidate genes reveals the molecular basis of cottonseed oil accumulation in Gossypium hirsutum L. - Zhibin Zhang; Juwu Gong; Zhen Zhang; Wankui Gong; Junwen Li; Yuzhen Shi; Aiying Liu; Qun Ge; Jingtao Pan; Senmiao Fan; Xiaoying Deng; Shaoqi Li; et al. (Theoretical and Applied Genetics, 2022)

Airborne black carbon variations during the COVID-19 lockdown in the Yangtze River Delta megacities suggest actions to curb global warming - Hao Li; Kan Huang; Qingyan Fu; Yanfen Lin; Jia Chen; Congrui Deng; Xudong Tian; Qian Tang; Qingchuan Song; Zhen Wei (Environmental Chemistry Letters, 2022)

Effect of Temperature on Macroscopic and Microscopic Properties of Sandstone From Qidong Coal Mine - Long-Chuan Deng; Xiao-Zhao Li; Ying-Chao Wang; Yun Wu; Zhen Huang; Chun-lu Jiang (Rock Mechanics and Rock Engineering, 2022)

Silencing of H19 alleviates oxygen–glucose deprivation/reoxygenation-triggered injury through the regulation of the miR-1306-5p/BCL2L13 axis - Yuxing Huang; Lisha Deng; Lin Zeng; Shanlin Bao; Kun Ye; Chengxun Li; Xiaolin Hou; Yuan Yao; Dingjun Li; Zhen Xiong (Metabolic Brain Disease, 2021)

Genetic and molecular characterization of determinant of six-rowed spike of barley carrying vrs1.a4 - Jin-Hui Wang; Zhen-Mei Xu; Xue-Bing Qiu; Li-Lan Li; Shui-Yang Yu; Tao Li; Yan-Yan Tang; Xi Pu; Juan-Yu Zhang; Hai-Li Zhang; Jun-Jun Liang; Ya-Wei Tang; et al. (Theoretical and Applied Genetics, 2021)

Integration and Potential Application Ability of Culturable Functional Microorganism in Oil Tea Camellia - Caixia Liu; Longsheng Chen; Zhilong He; Zhen Zhang; Yanming Xu; Zhigang Li; Yinghe Peng; Nan Deng; Yongzhong Chen (Indian Journal of Microbiology, 2021)

The impact of urbanization and consumption patterns on China’s black carbon emissions based on input–output analysis and structural decomposition analysis - Zhongci Deng; Ping Kang; Zhen Wang; Xiaoling Zhang; Weijie Li; Yihan Ou; Yu Lei; Ying Dang; Zhongren Deng (Environmental Science and Pollution Research, 2021)

Emerging chemical and physical disinfection technologies of fruits and vegetables: a comprehensive review - Li-Zhen Deng; Arun S. Mujumdar; Zhongli Pan; Sriram K. Vidyarthi; Jinwen Xu; Magdalena Zielinska; Hong-Wei Xiao (Critical Reviews in Food Science and Nutrition, 2020)

Variation of biogeochemical cycle of riverine dissolved inorganic carbon and silicon with the cascade damming - Haojun Deng; Zhen Tao; Quanzhou Gao; Ling Yao; Yong Feng; Yinhua Li; Jian Ding; Zhengang Wang; Xiaoxi Lyu; Peng Xu (Environmental Science and Pollution Research, 2020)

Time-resolved black carbon aerosol vertical distribution measurements using a 356-m meteorological tower in Shenzhen - Tianlin Sun; Cheng Wu; Dui Wu; Ben Liu; Jia Yin Sun; Xia Mao; Honglong Yang; Tao Deng; Lang Song; Mei Li; Yong Jie Li; Zhen Zhou (Theoretical and Applied Climatology, 2020)
Black carbon (BC) is an essential climate forcer in the atmosphere. Large uncertainties remain in BC’s radiative forcing estimation by models, partially due to the limited measurements of BC vertical distributions near the surface layer. We conducted time-resolved vertical profiling of BC using a 356-m meteorological tower in Shenzhen, China. Five micro-aethalometers were deployed at different heights (2, 50, 100, 200, and 350 m) to explore the temporal dynamics of BC vertical profile in the highly urbanized areas. During the observation period (December 6–15, 2017), the average equivalent BC (eBC) concentrations were 6.6 ± 3.6, 5.4 ± 3.3, 5.9 ± 2.8, 5.2 ± 1.8, and 4.9 ± 1.4 μg m −3 , from 2 to 350 m, respectively. eBC temporal variations at different heights were well correlated. eBC concentrations generally decreased with height. At all five heights, eBC diurnal variations exhibited a bimodal pattern, with peaks appearing at 09:00–10:00 and 19:00–21:00. The magnitudes of these diurnal peaks decreased with height, and the decrease was more pronounced for the evening peak. eBC episodes were largely initiated by low wind speeds, implying that wind speed played a key role in the observed eBC concentrations. eBC wind-rose analysis suggested that elevated eBC events at different heights originate from different directions, which suggested contributions from local primary emission plumes. Air masses from central China exhibited much higher eBC levels than the other three backward trajectory clusters found herein. The absorption Ångström exponent (AAE 375–880 ) showed clear diurnal variations at 350 m and increased slightly with height.

Synchrotron Radiation-Based Three-Dimensional Visualization of Angioarchitectural Remodeling in Hippocampus of Epileptic Rats - Pan Gu; Zi-Hao Xu; Yu-Ze Cao; Sheng-Hui Liao; Qian-Fang Deng; Xian-Zhen Yin; Zhuo-Lu Wang; Zhuo-Hui Chen; Xin-Hang Hu; Hui Wang; Li-Zhi Li; Shi-Xin Liu; et al. (Neuroscience Bulletin, 2020)

The giant Zaozigou Au-Sb deposit in West Qinling, China: magmatic- or metamorphic-hydrothermal origin? - Kun-Feng Qiu; Hao-Cheng Yu; Jun Deng; Duncan McIntire; Zong-Yang Gou; Jian-Zhen Geng; Zhao-Shan Chang; Rui Zhu; Kang-Ning Li; Richard Goldfarb (Mineralium Deposita, 2020)

The role of MAPK signaling pathway in formation of EMT in oral squamous carcinoma cells induced by TNF-α - Xiao-Wei Zhao; Jing-Ping Zhou; Yu-Lan Bi; Jia-Ying Wang; Rui Yu; Chao Deng; Wei-Kang Wang; Xian-Zhen Li; Rui Huang; Jili Zhang; De-Tao Tao (Molecular Biology Reports, 2019)

Quantitative trait locus mapping for plant height and branch number in an upland cotton recombinant inbred line with an SNP-based high-density genetic map - Zhen Zhang; Aiying Liu; Zhen Huang; Senmiao Fan; Xianyan Zou; Xiaoying Deng; Qun Ge; Juwu Gong; Junwen Li; Wankui Gong; Yuzhen Shi; Liqiang Fan; et al. (Euphytica, 2019)

Chemical and physical pretreatments of fruits and vegetables: Effects on drying characteristics and quality attributes – a comprehensive review - Li-Zhen Deng; Arun S. Mujumdar; Qian Zhang; Xu-Hai Yang; Jun Wang; Zhi-An Zheng; Zhen-Jiang Gao; Hong-Wei Xiao (Critical Reviews in Food Science and Nutrition, 2019)

Deletion of the Type IV Secretion System Effector VceA Promotes Autophagy and Inhibits Apoptosis in Brucella-Infected Human Trophoblast Cells - Jing Zhang; Min Li; Zhiqiang Li; Jingxue Shi; Yu Zhang; Xingmei Deng; Liangbo Liu; Zhen Wang; Yayin Qi; Hui Zhang (Current Microbiology, 2019)

Magnetic chitosan/sodium alginate gel bead as a novel composite adsorbent for Cu(II) removal from aqueous solution - Hu-Chun Tao; Shuo Li; Li-Juan Zhang; Yi-Zhen Chen; Li-Ping Deng (Environmental Geochemistry and Health, 2019)

Occurrence of Telenomus dignus (Gahan) on the Sugarcane Borers, Scirpophaga intacta Snellen and Chilo sacchariphagus Bojer in Guangxi Province, China - Zhen-Qiang Qin; François-Régis Goebel; De-Wei Li; Jin-Ju Wei; Xiu-Peng Song; Ya-Wei Luo; Lu Liu; Zhan-Yun Deng (Sugar Tech, 2018)

Age and geochemistry of Early Ordovician A-type granites in the Northeastern Songnen Block, NE China - Changzhou Deng; Deyou Sun; Guangyi Sun; Changlu Lv; Zhen Qin; Xianquan Ping; Guanghui Li (Acta Geochimica, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Impact of mixed anthropogenic and natural emissions on air quality and eco-environment—the major water-soluble components in aerosols from northwest to offshore isle - Yilun Jiang; Guoshun Zhuang; Qiongzhen Wang; Kan Huang; Congrui Deng; Guangyuan Yu; Chang Xu; Qingyan Fu; Yanfen Lin; Joshua S. Fu; Mei Li; Zhen Zhou (Air Quality, Atmosphere & Health, 2018)

Association of IL-28B, TBX21 gene polymorphisms and predictors of virological response for chronic hepatitis C - Dan Yan Zhu; Xiao Zhao Deng; Yu Meng Zhu; Guo Tao Li; Guo Qiang Zhang; Ling Ju Wang; Jing Hai Zhang; Wen Xiao; Zhen Xian Zhou; Wei Liang Ding (Archives of Virology, 2018)

Cloning and characterization of Agp1, the gene encoding the small subunit of ADP-glucose pyrophosphorylase from wheat and its relatives - Xiao-Wei Zhang; Qing Wang; Ling-Ling Zhang; Xiao-Juan Zhong; Qian-Tao Jiang; Jian Ma; Peng-Fei Qi; Wei Li; Guo-Yue Chen; Xiu-Jin Lan; Mei Deng; Zhen-Xiang Lu; et al. (Biologia, 2017)

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China - Hao Liu; Xin-Tong Li; Bo Hu; Xiao-Yu Deng; Lei Zhang; Shi-Zhen Lian; Hai-Ling Zhang; Shuang Lv; Xiang-Hong Xue; Rong-Guang Lu; Ning Shi; Ming-Hao Yan; et al. (Archives of Virology, 2017)

Identification and molecular characterization of one novel 1SPl-encoded s-type low molecular weight glutenin B-subunit from 1Sl(1B) substitution line of wheat variety Chinese Spring (Triticum aestivum) - Xiong Deng; Shun-li Wang; Shou-min Zhen; Wen-ying Zhang; Yue-ming Yan (Biologia, 2016)

Neprilysin Confers Genetic Susceptibility to Alzheimer’s Disease in Han Chinese - Hui-Zhen Wang; Rui Bi; Deng-Feng Zhang; Guo-Dong Li; Xiao-Hong Ma; Yiru Fang; Tao Li; Chen Zhang; Yong-Gang Yao (Molecular Neurobiology, 2016)

Se Enhances MLCK Activation by Regulating Selenoprotein T (SelT) in the Gastric Smooth Muscle of Rats - Jia-ping Li; Jing-xuan Zhou; Qi Wang; Gao-qin Gu; Shi-jin Yang; Cheng-ye Li; Chang-wei Qiu; Gan-zhen Deng; Meng-yao Guo (Biological Trace Element Research, 2016)

PD-1/PD-L1 signal pathway participates in HCV F protein-induced T cell dysfunction in chronic HCV infection - Wen Xiao; Long Feng Jiang; Xiao Zhao Deng; Dan Yan Zhu; Jia Ping Pei; Mao Lei Xu; Bing Jun Li; Chang Jun Wang; Jing Hai Zhang; Qi Zhang; Zhen Xian Zhou; Wei Liang Ding; et al. (Immunologic Research, 2016)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

Neuroprotective Effects of β-Asarone Against 6-Hydroxy Dopamine-Induced Parkinsonism via JNK/Bcl-2/Beclin-1 Pathway - Sheng Zhang; Xue-Hong Gui; Li-Ping Huang; Min-Zhen Deng; Ruo-Ming Fang; Xue-Hong Ke; Yu-Ping He; Ling Li; Yong-Qi Fang (Molecular Neurobiology, 2016)

The role of KCa3.1 channels in cardiac fibrosis induced by pressure overload in rats - Li-Mei Zhao; Li-Ping Wang; Hui-Fang Wang; Xiao-Zhen Ma; Dang-Xia Zhou; Xiu-Ling Deng (Pflügers Archiv - European Journal of Physiology, 2015)

HPLC pigment profiles of 31 harmful algal bloom species isolated from the coastal sea areas of China - Shuxia Liu; Peng Yao; Zhigang Yu; Dong Li; Chunmei Deng; Yu Zhen (Journal of Ocean University of China, 2014)

Molecular modeling study on the structural basis of binding mechanism of C6-substituted phthalides with monoamine oxidases - Pei Zhen Li; Yue Li Tian; Hong Lin Zhai; Fang Fang Deng; Mei Hong Xie; Xiao Yun Zhang (Medicinal Chemistry Research, 2014)

A three‐component signalling system fine‐tunes expression kinetics of HPPK responsible for folate synthesis by positive feedback loop during stress response of X anthomonas campestris - Fang‐Fang Wang; Chao‐Ying Deng; Zhen Cai; Ting Wang; Li Wang; Xiao‐Zheng Wang; Xiao‐Ying Chen; Rong‐Xiang Fang; Wei Qian (Environmental Microbiology, 2014)
Summary During adaptation to environments, bacteria employ two‐component signal transduction systems, which contain histidine kinases and response regulators, to sense and respond to exogenous and cellular stimuli in an accurate spatio‐temporal manner. Although the protein phosphorylation process between histidine kinase and response regulator has been well documented, the molecular mechanism fine‐tuning phosphorylation levels of response regulators is comparatively less studied. Here we combined genetic and biochemical approaches to reveal that a hybrid histidine kinase, SreS , is involved in the SreK ‐ SreR phosphotransfer process to control salt stress response in the bacterium X anthomonas campestris . The N ‐terminal receiver domain of SreS acts as a phosphate sink by competing with the response regulator SreR to accept the phosphoryl group from the latter's cognate histidine kinase SreK . This regulatory process is critical for bacterial survival because the dephosphorylated SreR protein participates in activating one of the tandem promoters ( P 2) at the 5′ end of the sreK ‐ sreR ‐ sreS ‐ hppK operon, and then modulates a transcriptional surge of the stress‐responsive gene hppK , which is required for folic acid synthesis. Therefore, our study dissects the biochemical process of a positive feedback loop in which a ‘three‐component’ signalling system fine‐tunes expression kinetics of downstream genes.

Citrus disease recognition based on weighted scalable vocabulary tree - Xiao-Ling Deng; Zhen Li; Xiao-Ling Deng; Tian-Sheng Hong (Precision Agriculture, 2014)

Advanced glycation end products impair KCa3.1- and KCa2.3-mediated vasodilatation via oxidative stress in rat mesenteric arteries - Li-Mei Zhao; Yan Wang; Xiao-Zhen Ma; Nan-Ping Wang; Xiu-Ling Deng (Pflügers Archiv - European Journal of Physiology, 2014)

Genes encoding the production of extracellular polysaccharide bioflocculant are clustered on a 30-kb DNA segment in Bacillus licheniformis - Shan Yan; Na Wang; Zhen Chen; Yuanpeng Wang; Ning He; Yajuan Peng; Qingbiao Li; Xu Deng (Functional & Integrative Genomics, 2013)

Functionalized single-walled carbon nanotubes cause reversible acute lung injury and induce fibrosis in mice - Yanli Zhang; Jiejie Deng; Yanxu Zhang; Feng Guo; Chenggang Li; Zhen Zou; Wen Xi; Jun Tang; Yang Sun; Peng Yang; Zongsheng Han; Dangsheng Li; et al. (Journal of Molecular Medicine, 2013)

Artificial Cold Wave-Induced Cerebral Infarction in Rats with Carotid Atherosclerosis - Zhen-Yu Tang; Qiu-Yan Zhu; Li-Jun Xu; Li-Ying Deng; Ying Zeng; Wei-Jiang Ding; Wei Huang (Journal of Molecular Neuroscience, 2012)

Amyloid beta–heme peroxidase promoted protein nitrotyrosination: relevance to widespread protein nitration in Alzheimer’s disease - Can Yuan; Lian Yi; Zhen Yang; Qingqing Deng; Yi Huang; Hailing Li; Zhonghong Gao (JBIC Journal of Biological Inorganic Chemistry, 2012)

Population genetic analysis of 15 autosomal STR loci in the Russian population of northeastern Inner-Mongolia, China - Bo-feng Zhu; Guang Yang; Chun-mei Shen; Hai-xia Qin; Shuan-liang Fan; Li-bin Deng; Feng Chen; Li-ping Chen; Hong-dan Wang; Zhen-yuan Wang; Rudolf Lucas; Zhen-min Lian (Molecular Biology Reports, 2010)

Characterization of a novel wheat NAC transcription factor gene involved in defense response against stripe rust pathogen infection and abiotic stresses - Ning Xia; Gang Zhang; Xin-Ying Liu; Lin Deng; Gao-Lei Cai; Yi Zhang; Xiao-Jie Wang; Jie Zhao; Li-Li Huang; Zhen-Sheng Kang (Molecular Biology Reports, 2010)

Distributions of HLA-A and -B alleles and haplotypes in the Yi ethnic minority of Yunnan, China: relationship to other populations - Bo-feng Zhu; Guang Yang; Chun-mei Shen; Hai-xia Qin; Shun-zhi Liu; Ya-jun Deng; Shuan-liang Fan; Li-bin Deng; Feng Chen; Ping Zhang; Jie Fang; Li-ping Chen; et al. (Journal of Zhejiang University-SCIENCE B, 2010)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

Cloning and Characterization of the SSB-1 and SSB-4 Genes Expressed in Zebrafish Gonads - Jian-Zhen Li; Ya-Ping Zhou; Yan Zhen; Yan Xu; Peng-Xiang Cheng; Huan-Nan Wang; Feng-Jiao Deng (Biochemical Genetics, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Isolation of Female-Specific AFLP Markers and Molecular Identification of Genetic Sex in Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Song-Lin Chen; Jing Li; Si-Ping Deng; Yong-Sheng Tian; Qing-Yin Wang; Zhi-Meng Zhuang; Zhen-Xia Sha; Jian-Yong Xu (Marine Biotechnology, 2007)